Atypical audio-visual neural synchrony and speech processing in early autism - Xiaoyue Wang; Sophie Bouton; Nada Kojovic; Anne-Lise Giraud; Marie Schaer (Journal of Neurodevelopmental Disorders)
Abstract Background Children with Autism Spectrum disorder (ASD) often exhibit communication difficulties that may stem from basic auditory temporal integration impairment but also be aggravated by an audio-visual integration deficit, resulting in a lack of interest in face-to-face communication. This study addresses whether speech processing anomalies in young autistic children (mean age 3.09-year-old) are associated with alterations of audio-visual temporal integration. Methods We used high-density electroencephalography (HD-EEG) and eye tracking to record brain activity and gaze patterns in 31 children with ASD (6 females) and 33 typically developing (TD) children (11 females), while they watched cartoon videos. Neural responses to temporal audio-visual stimuli were analyzed using Temporal Response Functions model and phase analyses for audiovisual temporal coordination. Results The reconstructability of speech signals from auditory responses was reduced in children with ASD compared to TD, but despite more restricted gaze patterns in ASD it was similar for visual responses in both groups. Speech reception was most strongly affected when visual speech information was also present, an interference that was not seen in TD children. These differences were associated with a broader phase angle distribution (exceeding pi/2) in the EEG theta range in children with ASD, signaling reduced reliability of audio-visual temporal alignment. Conclusion These findings show that speech processing anomalies in ASD do not stand alone and that they are associated already at a very early development stage with audio-visual imbalance with poor auditory response encoding and disrupted audio-visual temporal coordination.